When beavers flew : an incredible true story of rescue and relocation - Tracy, Kristen, 1972- (Random House Studio, 2024)
"This fascinating picture book tells the unique, quirky, and true story of how Elmo Heter saved 76 beavers from destroying a town in Idaho by parachuting them into uninhabited wetlands"--